2008
DOI: 10.1175/2008jcli2275.1
|View full text |Cite
|
Sign up to set email alerts
|

Rainfall Occurrence in the U.S. Warm Season: The Diurnal Cycle*

Abstract: The diurnal occurrence of warm-season rainfall over the U.S. mainland is examined, particularly in light of forcings at multiple scales. The analysis is based on a radar dataset of 12-seasons duration covering the U.S. mainland from the Continental Divide eastward. The dataset resolves 2-km features at 15-min intervals, thus providing a detailed view of both large-and regional-scale diurnal patterns, as well as the statistics of events underlying these patterns. The results confirm recent findings with respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
179
2
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(204 citation statements)
references
References 27 publications
22
179
2
1
Order By: Relevance
“…And the diurnal variation of the solenoid circulation may contribute to the longevity and propagation of episodes in the vicinity of the eastern TP. Bao et al (2011) employed the theory of mountain-plain solenoid propagation (may refer to Tripoli and Cotton 1989;Carbone and Tuttle 2008) to understand the phenomena of eastward delayed phase for precipitation in the Sichuan Basin. Chen et al (2010) and Yuan et al (2011) suggested that the summertime nocturnal precipitation was attributed to the decreasing stability caused by the low-tropospheric convergence and upward motion, accompanied by a long wave radiative cooling at the cloud top and the weak cold advection from the TP.…”
Section: Introductionmentioning
confidence: 99%
“…And the diurnal variation of the solenoid circulation may contribute to the longevity and propagation of episodes in the vicinity of the eastern TP. Bao et al (2011) employed the theory of mountain-plain solenoid propagation (may refer to Tripoli and Cotton 1989;Carbone and Tuttle 2008) to understand the phenomena of eastward delayed phase for precipitation in the Sichuan Basin. Chen et al (2010) and Yuan et al (2011) suggested that the summertime nocturnal precipitation was attributed to the decreasing stability caused by the low-tropospheric convergence and upward motion, accompanied by a long wave radiative cooling at the cloud top and the weak cold advection from the TP.…”
Section: Introductionmentioning
confidence: 99%
“…An overview of the process of precipitation retrieval from radar reflectivities over Great is known about how the radar precipitation composite performs over multi-annual scales. Some climatologies from radar-derived precipitation data have been created for the Himalayan region (Houze et al, 2007), USA (Carbone and Tuttle, 2008), The Netherlands (Overeem et al, 2009) and France (Tabary et al, 2012). Radar-based climatologies using space-based radar have also been performed (e.g.…”
mentioning
confidence: 99%
“…For example, Rudolph et al (2011) used a 9-year radar data set to investigate the relationship between precipitation and synoptic-scale weather patterns in the European Alps region, while Rudoplh and Friedrich (2013) have studied the vertical structure of precipitation and its seasonality. Previously Carbone and Tuttle (2008) used radar data over the mainland USA to examine the diurnal characteristics of rainfall and the meteorological conditions driving the diurnal cycle (esp. the role of propagating systems).…”
Section: A Devasthale and L Norin: Radar Observations Of Precipitatmentioning
confidence: 99%